3G internet and human capital development - Ronak Jain; Samuel Stemper (University of Zurich, Department of Economics, 2024)
We study the impact of global expansions in mobile internet access between 2000 and 2018 on student outcomes. We link geospatial data on the rollout of 3G mobile technology with over 2.5 million student test scores from 82 countries. Our findings indicate that the introduction of 3G coverage leads to substantial increases in smartphone ownership and internet usage among adolescents. Changes in 3G coverage lead to significant declines in test scores in math, reading, and science, with magnitudes roughly equivalent to the loss of one-quarter of a year of learning. We also find evidence of a reduction in the ease of making friends and a sense of belonging.
hdl:10.5167/uzh-262405
Keywords: I21; I25; I31; J24; L86; O33; 330